From Modernism to Metro Maps: Mondrian, Beck, and Salomon - Peter B. Lloyd (Janeway JS, 2017)
Many people have noted a suggestive parallel between the abstract paintings of Piet Mondrian and the design of metro maps such as Henry Beck’s map of the London Underground. Is this just a superficial similarity or is there some more substantive point of connection? This article speculates that the ‘dynamic equilibrium’, which gave Mondrian’s mature pictures their inimitable psychological force, could also be at work in the most iconic metro maps, such as those of Henry Beck and George Salomon. If so, then the automatic generation of metro maps to an acceptable quality may entail the daunting task of operationalising this dynamic balance and encoding it in computer software.
Keywords: Reformation; gender; Intertextuality